Perbedaan Penerapan Model Pembelajaran Sains Teknologi Masyarakat, Kontekstual dan Kooperatif Pada Mata Pelajaran IPS SD - Ivan Stevanus (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2010)
Abstract: This experimental research had a purpose to describe a difference implementation model of science of society technology, contextual, and cooperative in teaching social studies. The subjects of the research were students of fifth grade students of Bunda Mulia Kebun Elementary School Jeruk dan Tarakanita II Elementary School Kebayoran Baru Jakarta. The sample was collected by purposive random sampling. Results found: there was improvement of learning achevement after teachers implemented STM teaching model; there was improvement of learning achevement after teachers implemented contextual teaching model; there was improvement of learning achevement after teachers implemented cooperative teaching model. Among three models, the highest was contextual teaching model.